STUDI TENTANG PROSES PEMBUATAN KERAJINAN PERAK KOTO GADANG KABUPATEN AGAM - Rendhy Ryas Pratama, Dr. Yahya, M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2017)
The purpose of the study describes the types of materials, tools, and processes used in the manufacture of silverware in nagari (village) Koto Gadang Agam District. The process of making silver Koto Gadang still using traditional tools. The research method used qualitative descriptive. Data source used primary data and secondary data. Data collection by observation, interview, and documentation. Data analysis is done by: data reduction, data display (presentation of data), drawing conclusions, checking the validity of findings with triangulation technique. The result of observation and interview in nagari Koto Gadang Agam Regency, that the process of making silver Koto Gadang by using raw materials from silver seeds are looking for silver collectors. The processing of raw materials is done using traditional equipment until now.Kata Kunci: Pembuatan Kerajinan Perak